1984
DOI: 10.1139/x84-131
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic identification of clones in trembling aspen

Abstract: Electrophoretic techniques which can be used to aid the identification of clones are described. An example using members (putative ramets) from 10 morphologically distinct putative clones of trembling aspen is presented. In this example, it is demonstrated that phenotypically uniform groups of trees (putative clones) can actually be composed of several electrophoretically distinct genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 0 publications
1
43
1
2
Order By: Relevance
“…Cependant cette technique est soumise à certaines limites, notamment la difficulté de détecter certaines mutations qui n'affectent pas la charge de l'enzyme et la nécessité d'étudier un nombre élevé de marqueurs pour l'identification de clones ou de variétés très étroi-tement apparentés (Cheliak et Pitel, 1984 ;Chevreau, 1984).…”
unclassified
“…Cependant cette technique est soumise à certaines limites, notamment la difficulté de détecter certaines mutations qui n'affectent pas la charge de l'enzyme et la nécessité d'étudier un nombre élevé de marqueurs pour l'identification de clones ou de variétés très étroi-tement apparentés (Cheliak et Pitel, 1984 ;Chevreau, 1984).…”
unclassified
“…The same multilocus genotypes shared by clones N29 and N60 seems to be coincidental since these clones had distant origins in the Netherlands . However, these clones could be uniquely genotyped by exploring more Table 3 such as P. tremuloides (Cheliak & Pitel, 1984), P . deltoides, P. maximowiczii and P .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, isozyme polymorphism has been widely applied by plant breeders for identification and classification of cultivars and varieties of agricultural and related plants (e .g ., Fedak, 1974 ;Bassiri & Rouhani, 1977 ;Werner & Sink, 1977 ;Bassiri & Adams, 1978 ;Cardy & Kannenberg, 1982 ;Ignart & Weeden, 1984 ;Weeden, 1984 ;Nielsen, 1985 ;Nielsen & Johansen, 1986 ;Glaszmann, 1987 ;Ramirez et al ., 1987) . In forest trees, the application of isozyme analysis for identification of clones, cultivars and varieties has been limited (Miyazaki & Miyajima, 1981 ;Adams, 1983 ;Cheliak & Pitel, 1984 ;Rajora, 1986) . We have demonstrated allozymes as potential tools for clonal and cultivar identification of Populus deltoides, P. maximowiczii Henry and P .…”
Section: Introductionmentioning
confidence: 99%
“…Two loci were also reported in Populus spp. ( CHELIAK and PITEL 1984b;HYUN et al 1987;FARMER et al 1988;RAJORA 1990). Results suggested a Mendelian model of codominant inheritance in a two locitwo alleles per locus system.…”
Section: Acid Phosphatase (Acp)mentioning
confidence: 94%
“…Two PGI loci were also found in Populus spp. (CHELIAK and PITEL 1984b;HYUN et al 1987;RAJORA 1990), and in the willows of the Longifoliae section (BRUNSFELD et al 1991). Heterozygotes suggested that PGI is functionally dimeric in the leaves of S. exigua.…”
Section: -Phosphogluconate Dehydrogenase (6pgd)mentioning
confidence: 99%